Changes in the Quality Parameters of Wheat Samples of 16% Moisture Content during Storage - Győriné Mile, Irma (Acta Agraria Debreceniensis, 2003)
We have carried out storage experiments with wheat varieties Magvas, Fatima, Mv Emma and Mv Pálma from the 2001 growth year. During the first half of the experiments quality parameters, such as changes in moisture, protein and gluten contents as well as pharinograph readings, falling numbers and sedimentation indices were analysed and tested at an average initial moisture content of 13%. The findings in the changes in the quality parameters of different wheat varieties with 13% moisture content as a function of storage time duration were published in an earlier paper of mine (12/04/2002). This paper wishes to give an account of the second part of the storage test when the moisture contents of the different varieties were raised to 16% and the changes in the quality parameters were monitored for seven weeks. The findings show that contrary to what had been experienced in the first half of the trial, there were no changes in the protein contents, pharinograph readings, water uptake or Zeleny counts and falling numbers showed decreases with each of the varieties tested.